Product analysis of retail banking of BRAC Bank Ltd. : Joydevpur Branch, Gazipur - Razzak, Mohammed Abdur (BRAC university, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.